Reunifying Cyprus (London)
xii, 282 sayfa
Keywords: “Spring 2008 witnessed the first positive signs of a thaw in relations between the two sides of the divided island of Cyprus since the dramatic failure of the Annan Plan in 2004. The historic meeting of the Greek and Turkish Cypriot leaders and the symbolic opening of the Ledra Street border crossing in the heart of Nicosia may herald a bright new future for this Mediterranean island. Yet Cyprus has been in this situation before. What makes this new initiative different and why should it succeed where so many others have failed? “Reunifying Cyprus“ is the first book to analyse fully the reasons for the continuing failure to re-unite the two states of Cyprus after over forty years of division. It focuses especially on the Annan Plan - the popular name for the UN initiative to find a 'Comprehensive Solution to the Cyprus Problem' in anticipation of Cyprus' accession to the EU - and the reasons for its ultimate failure. How did Cypriots receive the Annan Plan? What were the real or imagined flaws? Was this a missed opportunity? And what place does the Annan Plan have in future blueprints to reunify the island? “Reunifying Cyprus“ will be invaluable for anyone interested in conflict resolution and international politics as well as students of the Eastern Mediterranean“ --